Enhanced energy storage properties of Sr(Ti0.5Zr0.5)O3 modified (Na0.5Bi0.5)TiO3 ceramics. (27th March 2022) - Zhang, Fanbo; Dai, Zhonghua; Pan, Yu; Chen, Guoshuai; Liu, JingJing; Liu, Weiguo; Karaki, Tomoaki
Summary: With the rapid development of electronic industry, the miniaturization and integration of components have become an irreversible development trend, which puts forward high requirements for lead‐free ceramic materials with excellent recoverable energy storage density and efficiency. In addition, it is also a great challenge to sustain excellent energy storage performance under different environmental conditions. In this work, a combined design strategy was proposed to induce polar nano regions and reduce grain size by introducing SrTi0.5 Zr0.5 O3 (STZ). The addition of STZ reduced the grain size to submicron level, accompanied by relaxation enhancement. The high energy storage properties ( W rec = 1.85 J/cm 3, η = 65.92%) were achieved in 0.80Bi0.5 Na0.5 TiO3 ‐0.20SrTi0.5 Zr0.5 O3 (BNT‐STZ) ceramics at 150 kV/cm. Excellent temperature stability (40°C‐160°C) and frequency stability (1‐500 Hz) of energy storage performance have been obtained under 100 kV/cm, with the fluctuations below 8%. Importantly, A high power density of 3.64 MW/cm 3 and a transitory discharge time ( t 0.9 0.632 μs) were achieved for 0.80BNT‐0.20STZ ceramic under 160 kV/cm. These characteristics indicate that 0.80BNT‐0.20STZ ceramic is expected to be applied in high‐power equipment. Highlights: A combined design strategy was proposed to induce polar nano regions and reduce grain size by introducing STZ. 0.80BNT‐0.20STZ ceramic possesses a recoverable energy density of 1.85 J/cm 3 and efficiency of 65.92%. 0.80BNT‐0.20STZ ceramic exhibits good electrical stability in wide frequency (1‐500 Hz) and temperature range (40‐160°C). A high power density ( P D ) of 3.64 MW/cm 3 and a transitory discharge time ( t 0.9 0.632 μs) can be achieved. Abstract : The addition of STZ reduced the grain size to submicron level, accompanied by relaxation enhancement. The high energy storage properties (Wrec = 1.85 J/cm 3, η = 65.92%) were achieved in 0.80Bi0.5 Na0.5 TiO3 ‐0.20SrTi0.5 Zr0.5 O3 (BNT‐STZ) ceramics at 150 kV/cm. Excellent temperature stability (40°C‐160°C) and frequency stability (1‐500 Hz) of energy storage performance have been obtained under 100 kV/cm, with the fluctuations below 8%.